2015
DOI: 10.1089/hum.2015.095
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Cardiovascular Gene Therapy and Vascular Biology

Abstract: Cardiovascular gene therapy aims to treat coronary and peripheral artery disease, heart failure, and arrhythmia. The chosen transgene, delivery method, gene therapy vector type, high-quality vector production, and dose are all determining factors of the therapeutic outcome. High-resolution vascular imaging and increased knowledge of vascular biology in physiological and pathological conditions enable the finding of novel molecular targets for cardiovascular gene therapy. Transgenic and knockout mouse models ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Achieving safe, long-term expression continues to prove a challenge in monogenic disorders (2). Within cardiovascular disease, VEGF gene therapy is being applied to coronary artery disease (13).…”
Section: What Is Gene Therapy? (B)mentioning
confidence: 99%
“…Achieving safe, long-term expression continues to prove a challenge in monogenic disorders (2). Within cardiovascular disease, VEGF gene therapy is being applied to coronary artery disease (13).…”
Section: What Is Gene Therapy? (B)mentioning
confidence: 99%
“…This technique, called therapeutic angiogenesis, has been trialed extensively for coronary artery ischaemia and is now reaching phase 3 trials. 82 Studies in large and small FGR animal models have confirmed the efficacy of this approach for improving fetal growth before birth. In normal sheep pregnancy, injection of Ad.VEGF (1 Â 10 11 particles), compared with injection of a control nonvasoactive vector, increased uterine artery volume blood flow within 7 days of injection, and long term, this increase in flow persisted for at least 4 weeks until the end of gestation.…”
Section: Maternal Vegf Gene Therapymentioning
confidence: 95%
“…Действительно, микропузырьки играют решающую роль в защите и транспорте эндогенных мРНК и уже были использованы для доставки синтетических, терапевтических мРНК (таких, как мРНК-21) [86]. Другими средствами доставки либо пре-мРНК (для повышения уровня мРНК) или противосмысловых мРНК (для снижения уровня мРНК) могут служить вирусы, предназначенные для генной терапии (такие как лентивирусы или адено-ассоциированные вирусы) [87]. Перспективными могут быть разработки и в области нанотехнологий; например, наночастицы золота со средним диаметром 13 нм были функционализированы монослоем алкилтиол-модифицированных двухцепочечных молекул РНК [88].…”
Section: заключениеunclassified